Neuromyths in Education: Prevalence among Spanish Teachers and an Exploration of Cross-Cultural Variation - Ferrero, Marta; Garaizar, Pablo; Vadillo, Miguel A. (Frontiers in Human Neuroscience, 2016)
Enthusiasm for research on the brain and its application in education is growing among teachers. However, a lack of sufficient knowledge, poor communication between educators and scientists, and the effective marketing of dubious educational products has led to the proliferation of numerous ‘neuromyths’. As a first step towards designing effective interventions to correct these misconceptions, previous studies have explored the prevalence of neuromyths in different countries. In the present study we extend this applied research by gathering data from a new sample of Spanish teachers and by meta-analysing all the evidence available so far. Our results show that some of the most popular neuromyths identified in previous studies are also endorsed by Spanish teachers. The meta-analytic synthesis of these data and previous research confirms that the popularity of some neuromyths is remarkably consistent across countries, although we also note peculiarities and exceptions with important implications for the development of effective interventions. In light of the increasing popularity of pseudoscientific practices in schools worldwide, we suggest a set of interventions to address misconceptions about the brain and education.